Answer:
x = -2/3, 1/3
Step-by-step explanation:
Step 1: Factor
(3x + 2)(3x - 1) = 0
Step 2: Find roots
3x + 2 = 0
3x = -2
x = -2/3
3x - 1 = 0
3x = 1
x = 1/3
Answer:
Step-by-step explanation:
factor ; (3x-1)(3x+2)=0
then make both 3x-1 and 3x+2 equal to 0
(3x-1)=0 solve 3x+2=0
+ 1 +1 -2 -2
_______ _______
3x = 1 3x = -2
x =1/3 x= -2/3
check for to make sure both solutions work by plugging back into the equation
Answer:
last option is correct
Step-by-step explanation:
A step that could be used to find the solution is substitution.
We can directly substitute for c in equation F
Since c= 2d + 1 from equation E, we can substitute directly in equation F and we will have 2d + 1 = 3d + 7
Answer:
12
Step-by-step explanation:
When you count the units it's 3, but because the scale factor is 4, you have to multiply it by that. 3 times 4 is 12.
Answer:
5
Step-by-step explanation:
Substitute the n for 8 in
( times n)+3
product means multiply, so
( times 8)+3
First multiply by 8 to get 2
12/x=4
12 divided by x equals 4